Emotional security and psychological distress among survivors of child sexual - Cantón-Cortés, David (My University, 2015)
According to the emotional security theory (EST), conflicts between parents can lead to emotional insecurity in their children, who are trying to regulate their exposure to conflicts in a maladjusted way and developing insecure representations of the relationship between their parents, resulting in a higher probability of their developing psychological difficulties. Also, according to the specific-linkage hypothesis, the symptomatology developed may depend on the specific pattern of emotional insecurity shown by the children. The EST identifies 3 patterns of child security in community samples: secure, preoccupied, and disengagement strategies. The aim of the present study was to examine the role of emotional security in the family system on the psychological distress of victims of child sexual abuse (CSA), analysing the differential effects of different patterns of emotional insecurity. The sample comprised 147 young adult female survivors of CSA. Emotional security was assessed with the Security in the Family System (SIFS) Scale and psychological distress with the Symptom Checklist-90-Revised (SCL-90-R). Results showed that the preoccupied strategy was related to every SCL-90-R subscale except interpersonal sensitivity and hostility, which were the only subscales related to the disengagement strategy. No relationship was found between the secure strategy and SCL-90-R scores. This study confirms the hypothesis that the emotional insecurity of CSA survivors is related to their psychological adjustment, thus confirming the specific-linkage hypothesis in this population.
Keywords: Niños - Abusos sexuales; Child sexual abuse; Emotional security